Long-term clinical outcomes in patients with a working diagnosis of myocardial infarction with non-obstructed coronary arteries (MINOCA) assessed by cardiovascular magnetic resonance imaging. (15th February 2022) - Ananthakrishna, Rajiv; Liang, Zach; Raman, Betty; Moran, John L.; Rajvi, Benita; Patil, Sanjana; Grover, Suchi; Bridgman, Cameron; Selvanayagam, Joseph B.
Abstract: Background: Myocardial infarction with non-obstructed coronary arteries (MINOCA) is a distinct entity among patients presenting with troponin-positive acute chest pain. We have previously reported on the incremental diagnostic capability of cardiovascular magnetic resonance (CMR) in this cohort. There is paucity of evidence on the long-term (> 5 years) clinical outcomes of these patients as graded by their acute CMR diagnosis. Methods and results: A total of 229 patients with a working diagnosis of MINOCA who underwent CMR assessment during the acute admission (2010–2017) were prospectively studied. The primary endpoint was major adverse cardiac events (MACE) defined as a composite of all-cause mortality and cardiovascular readmissions, identified from hospital and primary care records. CMR performed at a median of 6 days (IQR 2, 8) from presentation provided a diagnosis in 85% of the patients (38% myocarditis, 28% acute myocardial infarction and 19% Takotsubo cardiomyopathy). Over a median follow-up of 7.1 years (IQR 3.7, 8.2), 56 (24%) patients experienced a MACE. We found a strong association between CMR diagnosis and MACE (log rank 30.47, p < 0.001). In multivariate analysis, age (hazard ratio = 1.07; 95% confidence interval = 1.05, 1.10; p < 0.001) and CMR diagnosis of acute myocardial infarction (hazard ratio = 8.87; 95% confidence interval = 2.58, 30.4; p = 0.001) were independent predictors of MACE. Conclusions: In a large cohort of patients with a working diagnosis of MINOCA, one in four suffer a MACE during long-term clinical follow-up. CMR diagnosis of acute myocardial infarction and age were significant predictors of MACE even in the absence of significant coronary artery obstruction. Graphical abstract: Unlabelled Image Highlights: MINOCA is a distinct clinical entity with different pathophysiological causes. CMR is a key investigation in patients presenting with a working diagnosis of MINOCA. One in four patients suffer a MACE during long-term clinical follow-up. In patients with a working diagnosis of MINOCA, CMR diagnosis of AMI is a significant predictor of MACE.